The institutional ownership and corporate dividend policy in China: the responsiveness under the financing constraints - Chew, Kah Seng (2019)
This dissertation takes the listed companies in China's A-share main board market from year 2010 to 2017 to conduct an empirical study on the relationship between institutional shareholding level and corporate dividend level. In addition, this study took further steps to understand whether there is any change on the said influence after the classification of institutional investors into three trading style categories. Lastly, this dissertation also studied whether there is any difference in the dividend policy of listed companies under different financing constraints, included the aftershock of financial deleveraging campaign implemented by Chinese government after year 2015. To enhance robustness and obtain more meaningful results to this dissertation, few additional models have been conducted with additional control variables for specific factors that would affect dividend level and institutional holdings, together with additional dummy variables that characterized the impact of financing constraints and financial deleveraging campaign. The research conclusions showed that: Firstly, institutional investors' shareholdings have significantly increased the company's dividend level. Secondly, relative to speculative institutions, the involvement of robust (stable) institutions have resulted more significant boost to the company's dividend level. Thirdly, although the level of financing constraints at the company level did not affected the positive impact of institutional investors on the level of dividends, however it produced the regulatory effect on sensitivity. For companies with low financing constraints, the involvement of institutional investors resulted more pronounced effect on the level of dividends as compared to the companies with high financial constraints. Lastly, there is a positive connection showed between the financial market liquidity and company’s dividend level, due to the inverse relationship exhibited between the company's financing constraints and financial market liquidity. Ever since the Chinese government started the financial deleveraging campaign in year 2016, the degree of corporate financing constraints had increased. The promotion effect of institutional investors' shareholding levels on corporate dividends declined since then. The conclusions of this study have clear policy implications in the context of China as the regulatory authorities are currently vigorously developing the institutional investments and advocating the Chinese listed companies to pay dividends to investors.